P043 Small intestinal inflammation but not colitis drives pro-inflammatory nutritional antigen-specific T-cell response. (15th January 2020) - Rodríguez Sillke, Y; Schumann, M; Lissner, D; Branchi, F; Glauben, R; Siegmund, B
Abstract: Background: Inflammatory bowel disease (IBD) represents a dysregulation of the mucosal immune system. The pathogenesis of Crohn's disease (CD) and ulcerative colitis (UC) is linked to the loss of intestinal tolerance and barrier function. The healthy mucosal immune system has previously been shown to be inert against food antigens. Since the small intestine is the main contact surface for antigens and therefore the immunological response, the present study served to analyse food-antigen-specific T cells in the peripheral blood of IBD patients. Methods: Peripheral blood mononuclear cells of CD, with an affected small intestine, and UC (colitis) patients, either active or in remission, were stimulated with the following food antigens: gluten, soybean, peanut and ovalbumin. Healthy controls and celiac disease patients were included as controls. Antigen-activated CD4 + T cells in the peripheral blood were analysed by a magnetic enrichment of CD154 + effector T cells and a cytometric antigen-reactive T-cell analysis ('ARTE' technology) followed by characterisation of the effector response. Results: The effector T-cell response of antigen-specific T cells were compared between CD with small intestinal inflammation and UC where inflammation was restricted to the colon. Among all tested food antigens, the highest frequency of antigen-specific T cells (CD4 + CD154 + ) was found for gluten. Celiac disease patients were included as control, since gluten has been identified as the disease-causing antigen. The highest frequency of gluten antigen-specific T cells was revealed in active CD when compared with UC, celiac disease on a gluten-free diet (GFD) and healthy controls. Ovalbumin-specific T cells were almost undetectable, whereas the reaction to soybean and peanut was slightly higher. But again, the strongest reaction was observed in CD with small intestinal involvement compared with UC. Remarkably, in celiac disease on a GFD only antigen-specific cells for gluten were detected. These gluten-specific T cells were characterised by up-regulation of the pro-inflammatory cytokines IFN-γ, IL-17A and TNF-α. IFN-g was exclusively elevated in CD patients with active disease. Gluten-specific T-cells expressing IL-17A were increased in all IBD patients. Furthermore, T cells of CD patients, independent of disease activity, revealed a high expression of the pro-inflammatory cytokine TNF-α. Conclusion: The 'ARTE'-technique allows to analyse and quantify food antigen specific T cells in the peripheral blood of IBD patients indicating a potential therapeutic insight. These data provide evidence that small intestinal inflammation in CD is key for the development of a systemic pro-inflammatory effector T-cell response driven by food antigens.